The tibialis anterior tendon revisited: a unified classification framework across development, evolution, and clinical application - Olewnik, Łukasz; Landfald, Ingrid C.; Ciechanowska, Magdalena; Abreu, Bento João; Cavalcante, Judney Cley (Frontiers in Cell and Developmental Biology, 2025)
The tibialis anterior tendon (TAT), the terminal extension of the tibialis anterior muscle (TAM), plays a key role in dorsiflexion and inversion of the foot. Although the TAM exhibits morphological constancy, its tendon demonstrates substantial variability in distal insertion patterns, with direct implications for radiological interpretation, surgical approaches, and anatomical education. This review synthesizes evidence from developmental anatomy, cadaveric dissection, and high-resolution imaging to propose a unified six-type classification of the TAT. The framework integrates fetal, adult, and ultrasonographic findings and highlights the significance of Types V and VI as the most surgically accessible and structurally consistent variants. Bifid and trifid insertion patterns (Types I–IV) may contribute to mediolateral foot control and demonstrate functional adaptation, particularly in the context of human bipedal locomotion. Comparative anatomical analysis across vertebrates reveals an evolutionary trajectory from simple dorsal muscle structures in amphibians and reptiles to specialized bifid insertions in primates and humans. Type VI may represent a recently derived morphology with possible functional redundancy. From a diagnostic standpoint, knowledge of TAT variants is essential to prevent misinterpretation of anatomical bifurcations as tendinopathy or partial tears in ultrasound and MRI assessments. Clinically, the classification aids in tendon transfer planning, especially for foot drop correction and reconstructive procedures. We recommend this unified classification as a reference standard for anatomical teaching, clinical diagnostics, and preoperative decision-making. Future research should include three-dimensional modeling of insertion geometry, biomechanical simulations of tendon function across types, and longitudinal studies tracking the ontogeny of TAT morphology.